77 INCONTINENCE AND DECONDITIONING IN A NONFRAIL SAMPLE OF INPATIENTS AT A UNIVERSITY TEACHING HOSPITAL. (18th November 2021) - Gorey, S; McAteer, C; Antonenko, A; Abrahams, E; Cameron, S; Egan, A; Ero, A; Fraser, C; Tey, Z H; Boochoon, L; Koay, W J; Sitram, R; et al.
Abstract: Background: Incontinence occurs in 26% of hospitalised adults 1 . Deconditioning in hospitalised adults is common and contributes to increased hospital stay 2 . The #endpjparalysis movement motivates us to reduce harms of hospitalisation older adults. Methods: We surveyed inpatients to capture the point prevalence of incontinence. We also collected information regarding functional status, continence status and use of continence wear. Local ethical review-board approval was obtained. All participants provided informed consent. Results: There were 86 responses. Mean age of participants was 71.5 years. 45.4% were female, >95% were admitted from home and were functionally independent. Mean length of stay for respondents was 7.4 days ±12. The median Clinical Frailty Scale, for respondents aged >65 years, was 3, indicating this cohort is not frail. 17 respondents reported incontinence on the day of survey; 8 of these reported that incontinence was a new experience for them since their admission. 24 respondents wore incontinence wear at home, 31 were wearing incontinence wear on the day of survey. Of 80 respondents who could toilet independently at home, 23 (26%) reported a new dependency to toilet. Of 83 respondents who mobilised independently at home (with or without an aid), 11 reported needing assistance of one-person to walk, 3 needed the assistance of two-people to walk or stand, five people required a hoist, while 3 were bedbound on the day of survey. Conclusion: We describe increased dependency in mobility, toileting and increased use of continence wear in non-frail hospitalised older adults. Future work is needed to maintain function during admission to hospital. References: 1. Condon, M., et al. (2019). 'Urinary and Faecal Incontinence: Point Prevalence and Predictors in a University Hospital.' Int J Environ Res Public Health 16. 2. Guilcher, S., et al. (2021). 'A qualitative study exploring the lived experiences of deconditioning in hospital in Ontario, Canada.' BMC Geriatrics 21.